Animal welfare in a pandemic what does COVID-19 tell us for the future? - Hancock, John T.; Rouse, Ros C.; Craig, Tim J. (CRC Press, Taylor & Francis Group, 2024)
"Animal Welfare in a Pandemic explores the impact of COVID-19 on a wide array of animals, from those in the wild to companion and captive animals. During the height of the pandemic, a range of animals were infected, and many died, but this was hard to predict, even using up-to-date bioinformatics. Lockdowns around the world had, and continue to have, a major effect on animals’ welfare, influencing pet ownership and care, as well as impacting on the work of conservation institutes due to the lack of visitors and funding and lack of tourist presence in the wild which impacted on anti-poaching efforts. Some of the vast amount of personal protection equipment (PPE) that was distributed was discarded, creating both dangers and occasional opportunities for wild animals. With the rollout of human vaccines, some countries started developing animal vaccines, only some of which were deployed. In summary, the pandemic had a wide-ranging influence on animal welfare around the world. This is reviewed to highlight what can be learned to protect and enhance animal welfare in future epidemics/pandemics, and contribute to a genuinely One Health approach where the health and welfare of both humans and animals are considered holistically. This book is authored by members of the University of the West of England, Bristol, who span a range of expertise in Biological Sciences, Social Sciences, Animal Welfare, and Ethics."
Keywords: Pandemie; Tierschutz; COVID-19; Tiere